POTRET TANTANGAN DAN STRATEGI PENGEMBANGAN PENDIDIKAN DI WILAYAH PERBATASAN INDONESIA - Komari, Komari; Aslan, Aslan; Rusiadi, Rusiadi (Berajah Journal, 2025)
This study aims to identify challenges and formulate strategies for developing education in Indonesia's border regions through a literature review. The results of the study indicate that education in border regions faces various obstacles, such as limited infrastructure, a shortage of qualified teachers, a lack of facilities and infrastructure, and low motivation to learn due to socio-cultural and geographical factors. Development strategies that can be implemented include the development of educational infrastructure, strengthening contextual curricula, improving teacher capacity and welfare, utilizing educational technology, and empowering communities and multisectoral collaboration. The implementation of integrated and sustainable strategies is expected to accelerate the equalisation of access to and quality of education in border areas, while strengthening the identity and national awareness of the younger generation.